Optic Atrophy Secondary to Preseptal Cutaneous Anthrax: Case Report. (August 2014) - Ekinci, Metin; Çağatay, H. Hüseyin; Hüseyinoğlu, Nergiz; Ceylan, Erdinç; Gökçe, Gökçen
Abstract Bacillus anthracis, the agent of anthrax, is a nonmotile, aerobic gram-positive rod that can form very resistant spores in economically poor environments. Anthrax can manifest as cutaneous, gastrointestinal, or inhalational form. Cutaneous anthrax, caused by direct skin contact, presents with eschar, lymphadenopathy, and a febrile illness. The face and eyelids are most commonly involved in cutaneous anthrax. A 45-year-old man was admitted to our clinic with high fever and swelling of the right eyelid. One day later on re-examination, formation of ulcerous lesions in the right medial canthal region was observed, with general oedema in the upper and lower eyelids. The patient was evaluated as having cutaneous anthrax and medical treatment was continued until the 28th day; he was discharged from the hospital with no loss of vision. He returned for a follow-up examination after 2 months, with decreased visual acuity (<logMAR 1.0). In the fundus examination, optic atrophy was observed. The patient was evaluated as having toxic optic neuropathy.